1965
DOI: 10.1017/s0022172400045083
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary changes in myxoma virus in Britain: An examination of 222 in naturally occurring strains obtained from 80 counties during the period October–November 1962

Abstract: Samples of lesions containing viable myxoma virus were collected from 222 infected wild rabbits captured in 80 counties of Britain during October–November 1962. They were dispatched by air to Australia and passaged once in domestic rabbits before being tested for their virulence by the intradermal inoculation of groups of six laboratory rabbits with small doses of virus.The results showed that a wide range of viruses of differing properties now coexist in Britain. Their virulence ranges from very high (99 % le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Britain (Fenner & Chapple, 1965;Fenner & Ratcliffe, 1965;Marshall & Fenner, 1960). Experiments by Fenner, Day & Woodroofe (1952) indicated that transmission of myxoma virus by mosquitoes, the principal vectors of myxomatosis in Australia, was an example of mechanical transmission.…”
Section: I6mentioning
confidence: 99%
“…Britain (Fenner & Chapple, 1965;Fenner & Ratcliffe, 1965;Marshall & Fenner, 1960). Experiments by Fenner, Day & Woodroofe (1952) indicated that transmission of myxoma virus by mosquitoes, the principal vectors of myxomatosis in Australia, was an example of mechanical transmission.…”
Section: I6mentioning
confidence: 99%
“…The development of resistance to myxomatosis in British wild rabbits is not unexpected, because of the earlier Australian results, and it is an example of one side of the natural accommodation of a virus-host relationship; the other side being the attenuation of the virus (Marshall & Fenner, 1960;Fenner & Chapple, 1965). How quickly and how far this accommodation is likely to go are questions which cannot yet be answered, but our knowledge of the relationship between myxoma virus and Oryctolagus over the last 25 years indicate that the process will probably be fairly slow.…”
Section: Resultsmentioning
confidence: 92%
“…In Australia and in Great Britain, moderately attenuated strains of virus quickly became the most common strains found in the field (Marshall & Fenner, 1960;Fenner & Chapple, 1965). It is believed that this state of affairs has continued and that further attenuation has not occurred, because strains of moderate virulence are more efficiently transmitted than strains of higher or lower virulence (Fenner, Day & Woodroofe, 1956;Mead-Briggs & Vaughan, 1975).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences of the immune status of the sire have not yet been determined and in this regard it should be noted that the wild rabbits from Urana in the above study were all sired by bucks which had never been infected, whereas all the selected domestic rabbits had sires which had recovered from myxomatosis. Before the epidemiological consequences of the age effect can be evaluated it will be necessary to show that it occurs where more attenuated virus strains are used, since infection in the field at present is largely by strains of Grade III virulence (Fenner & Chapple, 1965). However, since selection in wild rabbits with attenuated strains of virus and in domestic rabbits with more virulent strains have both resulted in a similar age effect to SS it seems likely that this age effect will be expressed for virus strains other than SS.…”
Section: Discussionmentioning
confidence: 99%